Corrosion and passivity of copper in solutions containing sodium sulphide : Analysis of potentiostatic current transients - Vásquez Moll, Víctor Dennis (1985)
The electrochemical behaviour of copper electrodes in NaOH solutions with the addition of Na2S was studied through the analysis of current transients under constant potential and complementary voltammetric and scanning electron microscopy data including energy dispersive X-ray analysis. The overall process can be described by the following three stages. The first stage corresponds to the nucleation and growth of a complex copper sulphide layer at potential values close to the equilibrium potentials of the Cu/Cu2S and Cu/Cu2S reversible electrodes. The second stage is related to the rupture of the copper sulphide film at potentials more positive than a certain critical value leading to pitting corrosion of copper metal and yielding a poorly protective copper sulphide layer. The third stage occurs in the copper oxide electroformation range, where the presence of copper sulphide accelerates the electrodissolution of the base metal and copper oxide hinders the sulphidization processes. The current transients of each stage are interpreted through a model based on the nucleation and growth mechanism.